Penerapan Kombinatorik pada Persamaan Diophantine Linier - A’lailliyyin1, A’lailliyyin; Amalia, Rica; Yulianto, Tony (Universitas Islam Madura, 2022)
In this paper we apply combinatoric principle on linear diophantine equation. The method being used on this research is theoritic method. Generally, the linear diophantine equation is a polynomial equation. The form of equation being solved in this paper is linear diophantine equation. As for the solution of this equation is limited to natural numbers and whole numbers. By using the combinatoric principle, we got the number of solution of these linear diophantine equation which is the combination for natural numbers solution and for whole numbers solution.